20 Apical ischaemia is ubiquitous in apical hypertrophic cardiomyopathy and occurs before overt hypertrophy. (1st November 2021) - Hughes, Rebecca K; Augusto, João B; Knott, Kristopher; Seraphim, Andreas; Joy, George; Mohiddin, Saidi; Captur, Gabriella; Lopes, Luis R; Kellman, Peter; Moon, James C
Abstract : Background: Small vessel disease and associated microvascular ischaemia is a key feature of hypertrophic cardiomyopathy (HCM). Perfusion defects are described in 41–79% of cases 1, 2 . Apical HCM (ApHCM) has features suggesting distinction from other HCM phenotypes (ECG, arrhythmogenicity, genotype, scar pattern, natural history). Clinically, apical hypoperfusion is frequently observed in ApHCM. We hypothesised that quantitative perfusion would be different and distinct in apical HCM. Methods and Results: Patients: 100 subjects with ApHCM, 50 with conventional HCM and 28 healthy volunteer controls. 33 of the ApHCM had 'relative ApHCM' – MWT<15 mm but other key features of the disease – typical ECG, apex thicker than septum with loss of apical tapering and apical systolic cavity obliteration. CMR: Quantitative perfusion mapping CMR using adenosine vasodilator stress. A visual read plus global and regional map segmentation was performed, with results expressed as myocardial blood flow (MBF, ml/g/min) and myocardial perfusion reserve (MPR). Results: Of 100 ApHCM, all (100/100) had apical perfusion defects on visual read. There was also a high prevalence of perfusion defects in conventional HCM (45/50, 90%, p=0.012), typically in hypertrophied areas. There were no defects in controls (P<0.005). Compared with HCM, global stress MBF in ApHCM was equivalent (mean (IQ range) 1.71 ml/g/min (1.48–2.06) vs 1.61 ml/g/min (1.31–2.08), P=0.436) and lower than controls (2.59 ml/g/min (2.28–2.96), P<0.005. The reduction in MBF was most pronounced in the apical segments in ApHCM vs HCM (1.27 ml/g/min (1.05–1.64) vs 1.59 ml/g/min (1.25–2.06 ml/g/min), P<0.005) and controls (2.54 ml/g/min (2.34–3.35), P<0.005). The defects were profound with flow reduction during stress being common (MPR<1). Flow reductions were less for relative ApHCM than overt ApHCM (global stress MBF 2.03 ml/g/min (1.71–2.24) vs 1.62 (1.36–1.89), P<0.005), and similarly, relative ApHCM had less scar than overt ApHCM (FWHM LGE 0.0g (0.0–7.0) vs 24.1g (14.2–35.7), P<0.005; 0.0% (0.0–7.6) vs 17.4% (11.0–23.4%), P<0.005). Conclusions: Apical microvascular ischaemia appears the hallmark feature of ApHCM, occurring even when the apical hypertrophy does not reach conventional diagnostic criteria (relative ApHCM).